2007
DOI: 10.1186/ar2297
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 induces human osteoclastogenesis via IL-17 in vitro, and anti-IL-23 antibody attenuates collagen-induced arthritis in rats

Abstract: This study demonstrates that IL-23 stimulates the differentiation of human osteoclasts from peripheral blood mononuclear cells (PBMC). Furthermore, in vivo blockade of endogenous IL-23 activity by treatment with anti-IL-23 antibody attenuates collagen-induced arthritis in rats by preventing both inflammation and bone destruction. IL-23 induced human osteoclastogenesis in cultures of PBMC in the absence of osteoblasts or exogenous soluble-receptor activator of NFkappaB ligand (RANKL). This IL-23-induced osteocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(122 citation statements)
references
References 35 publications
6
110
2
4
Order By: Relevance
“…In a pathogenic setting, IL-23 is known to enhance the effector functions of Th17 cells (19,20,50,51), as well as IL-23R + gd T cells (18,22,52). Our data are in line with studies by Yago et al, who demonstrated that IL-23 stimulates human osteoclast differentiation indirectly via Th17 cell activation (53). We demonstrated that the osteoclastogenic potential of T cells from the periphery was enhanced when cells were either precultured with IL-23 or derived from IL-23-rich arthritic joints.…”
Section: Discussionsupporting
confidence: 82%
“…In a pathogenic setting, IL-23 is known to enhance the effector functions of Th17 cells (19,20,50,51), as well as IL-23R + gd T cells (18,22,52). Our data are in line with studies by Yago et al, who demonstrated that IL-23 stimulates human osteoclast differentiation indirectly via Th17 cell activation (53). We demonstrated that the osteoclastogenic potential of T cells from the periphery was enhanced when cells were either precultured with IL-23 or derived from IL-23-rich arthritic joints.…”
Section: Discussionsupporting
confidence: 82%
“…However, IL-23 alone did not induce osteoclast formation. A previous study suggested that IL-23 was capable of inducing osteoclast formation in the absence of RANKL [49]. However, as enriched rather than pure cell populations were used, a contribution from other sources such as T cells could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…IL-23 is involved in the pathobiology of numerous chronic diseases, including colitis, encephalitis, psoriasis, rheumatoid arthritis and cancer 12,14,15,34 , and is critical for the survival of T H -17 cells 12,30 . These T cells release IL-17A, a cytokine that increases production of several proinflammatory molecules, including IL-1 and TNF 35 .…”
Section: Discussionmentioning
confidence: 99%